Survei Servant Leadership dalam Organisasi Kemahasiswaan dan Unit Kegiatan Mahasiswa - Sinuraya, Candra; Wirayanti, Triratri Talenta (Zenit, 2013)
The  purpose of the research is to know how important and how acceptable a servant leadership for the students who have applied this concept in their organization life. The respondents are 200 university students who were involved in student organization and student extra-curricular in several universities  in DKI Jakarta and Bandung. This observation uses conceptual framework to measure the servant leadership that is offered  by Wong and Page (2003) and uses five dimensions of Barbuto and Wheeler (altruistic calling, emotional healing, persuasive mapping, wisdom, organizational stewardship) as well as the three  dimensions, namely service, humility, and vision. The result of this observation shows that the servant leadership is important. Students who are involved in student organization admit that they have applied the eight dimensions of servant leadership in organizational life. Overall, the study shows that  the present leadership in the organizational life of students in several universities in Indonesia have led to servant leadership  Keywords: servant leadership, student organization and student extra-curricular.